Alegrias, tristezas e o que mais entre os membros de empresas familiares? - Setton, Ronald (2021)
This work aimed to understand the relational aspects that are present among members of a family who work in their family businesses. Many of these aspects interfere directly or indirectly in the life and in the constitution of the subjectivity of these people. These concerns justify the performance of this work, seeking to respond to a gap in studies of family businesses. There are several studies, research and statistics on economic, market, organizational and relationships with employees in family businesses. However, there are few studies on how the wishes and perspectives of family members and their interactions reflect on the functioning of the company and vice versa. It was a qualitative investigation, involving 8 (eight) participants, partner-owners and active in their family businesses, in which we sought to identify the relationships present between members, in the family and in the family business. It was found that from a systemic point of view, a double or triple position often causes conflicts, and relational difficulties appear among family members. Given the complexity of these systems, we were able to observe results that lead both to the direction of prevention and growth, and to the direction of psychological suffering. One of the results evidenced was the appropriation of the family business as a space of affection among family members, being subject to variations that may happen in family relationships, especially as regards the entry of households, wives, husbands, brothers-in-law and similar. We suggest that further research with family business members be carried out, deepening scientific knowledge for this area of great importance for our society